2006
DOI: 10.1111/j.1471-4159.2006.04155.x
|View full text |Cite
|
Sign up to set email alerts
|

A ubiquitin ligase HRD1 promotes the degradation of Pael receptor, a substrate of Parkin

Abstract: It has been proposed that in autosomal recessive juvenile parkinsonism (AR-JP), a ubiquitin ligase (E3) Parkin, which is involved in endoplasmic reticulum-associated degradation (ERAD), lacks E3 activity. The resulting accumulation of Parkin-associated endothelin receptor-like receptor (Pael-R), a substrate of Parkin, leads to endoplasmic reticulum stress, causing neuronal death. We previously reported that human E3 HRD1 in the endoplasmic reticulum protects against endoplasmic reticulum stress-induced apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
74
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 45 publications
(102 reference statements)
3
74
0
Order By: Relevance
“…The E3 ubiquitin ligase Hrd1 is required for the ubiquitination and degradation of many ERAD substrates (8,(24)(25)(26)(27)(28)…”
Section: Resultsmentioning
confidence: 99%
“…The E3 ubiquitin ligase Hrd1 is required for the ubiquitination and degradation of many ERAD substrates (8,(24)(25)(26)(27)(28)…”
Section: Resultsmentioning
confidence: 99%
“…HRD1 promotes ubiquitination and degradation of Pael-R by recognizing its unfolded state. Suppression of HRD1 expression results in accumulation of unfolded Pael-R and ER stress-mediated apoptosis (38). These results suggest that functional loss of other E3s, including HRD1, is implicated in the dysfunctional Parkin-induced neurodegeneration in autosomal recessive juvenile parkinsonism.…”
Section: Hrd1 and Neurodegenerative Diseasementioning
confidence: 81%
“…We have shown that HRD1 is widely expressed in the substantia nigra and is partially coexistent with dopaminergic neurons (9). We have also shown that HRD1 is localized in the hippocampus, cerebral cortex, striatum, globus pallidus, and Purkinje cells of the cerebellar cortex (11).…”
mentioning
confidence: 82%
“…HRD1 is an E3 ubiquitin ligase localized in the ER and expressed during ER stress; it protects against ER stress-induced apoptosis (7,8). Furthermore, we have previously demonstrated that HRD1 promotes ubiquitination and degradation of Parkin-associated endothelin receptor-like receptor (Pael-R), a substrate for Parkin, and suppresses Pael-Rinduced ER stress and apoptosis (9). HRD1 is a central member of the ubiquitin ligase complexes that are responsible for the recognition and ubiquitination of misfolded proteins in the ER for subsequent degradation by proteasomes (10).…”
mentioning
confidence: 99%